Pregled učinkovin v zdravljenju ran - Anderluh, Marko (Farmacevtski vestnik, 2016)
The article provides a systematic overview of drugs used in the treatment of wounds. Its purpose is not to give treatment guidelines for specific types of wounds, but rather to review mechanisms of drug action according to the individual phases of wound healing and to present current information on active ingredients that are currently registered or are available in the Republic of Slovenia. In this way, health professionals may select appropriate knowledgebased therapies in the process of wound care.
Keywords: anatomsko-terapevtsko-kemična klasifikacija zdravi; zaviralci agregacije trombocitov; zdravljenje ran; zdravljenje, ki temelji na znanju